L’identità narrativa ricœuriana alla prova del «nouveau roman» di Robbe-Grillet (ENTHYMEMA, 2013)
The present essay aims to connect Ricœur’s notion of narrative identity – developed between the 1980s and 1990s – with the nouveau roman theorized by Alain Robbe-Grillet in writings published between 1956 and 1963 and then collected in Pour un noveau roman. In the first part, the essay will summarize Ricœur’s  Aristotelian –apocalyptic narratology model in the light of a comparison with the work of Frank Kermode. In the second part, noveau roman’s ontic realism will be presented. Finally, in the third part, starting with a comparison with the world of computer games, the essay will trace the effect of the overlapping of noveau roman with narrative identity both on the level of description and prescription.